2018
DOI: 10.1080/15459624.2018.1479065
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a novel real-time respirator seal integrity monitor on firefighters: Simulated workplace pilot study

Abstract: Millions of workers, including firefighters, use respiratory protective device. The key aspect in assuring the intended protection level of a respirator is its fit. However, even if the respirator originally fits well, the faceseal may be breached during its use. Until now, there have been no practically viable, inexpensive means to monitor the performance of a respirator during actual use. A novel Respirator Seal Integrity Monitor (ReSIM) was developed and recently evaluated on manikins by our team. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Also, even if the respirator originally fit well, the face seal may be breached during use. 7 Factors including physical activity, ventilatory rate, and head and body movements influence particle entry through face seal leaks. 2 Some studies have also suggested that N95 respirators fail to protect HCWs during strenuous activities such as performing chest compressions.…”
Section: Discussionmentioning
confidence: 99%
“…Also, even if the respirator originally fit well, the face seal may be breached during use. 7 Factors including physical activity, ventilatory rate, and head and body movements influence particle entry through face seal leaks. 2 Some studies have also suggested that N95 respirators fail to protect HCWs during strenuous activities such as performing chest compressions.…”
Section: Discussionmentioning
confidence: 99%
“…The RePM developed in this effort is an improved version of the ReSIM, which was introduced and validated earlier (Lepp€ anen et al 2018;Wu et al 2018). Both the ReSIM and RePM deploy the optical lightscattering principle and are capable of counting particles of $0.3 lm and larger.…”
Section: Repmconcept and Designmentioning
confidence: 99%
“…A new concept integrated in a novel Respirator Seal Integrity Monitor (ReSIM) allowing a real-time monitoring of the respirator performance was recently developed and validated by Grinshpun and his University of Cincinnati team (Lepp€ anen et al 2018;Liu et al 2018;Wu et al 2018). However, this monitor utilizes a qualitative approach and was tested for FFRs only, not for PAPRs.…”
Section: Introductionmentioning
confidence: 99%